The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1139/cjce-2020-0656
|View full text |Cite
|
Sign up to set email alerts
|

Exploring vehicle probe data as a resource to enhance network-wide traffic volume estimates

Abstract: Annual average daily traffic (AADT) is a fundamental input for numerous civil engineering applications, yet generating reliable estimates of AADT at a network-wide level poses challenges. This article explores the potential use of vehicle probe data to enhance conventional traffic monitoring practice for generating network-wide estimates of AADT by exploring relationships between site-specific traffic volume data and vehicle probe data collected in Manitoba, Canada. The analysis revealed that mean travel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Zhang and Chen ( 14 ) found a very strong correlation between overall traffic volumes and probe vehicle counts. Grande et al ( 18 ) found that truck volumes exhibited a similarly strong relationship. No previous study has accounted for this important feature.…”
mentioning
confidence: 94%
“…Zhang and Chen ( 14 ) found a very strong correlation between overall traffic volumes and probe vehicle counts. Grande et al ( 18 ) found that truck volumes exhibited a similarly strong relationship. No previous study has accounted for this important feature.…”
mentioning
confidence: 94%